The implications of exercise in Drosophila melanogaster: insights into Akt/p38 MAPK/Nrf2 pathway associated with Hsp70 regulation in redox balance maintenance. - Dahleh, M.M.M.; Araujo, S.M.; Bortolotto, V.C.; Torres, S.P.; Machado, F.R.; Meichtry, L.B.; Musachio, E.A.S.; Guerra, G.P.; Prigol, M. (Journal of comparative physiology. B, Biochemical, systemic, and environmental physiology, 2023)
This study investigated the potential effects of exercise on the responses of energy metabolism, redox balance maintenance, and apoptosis regulation in Drosophila melanogaster to shed more light on the mechanisms underlying the increased performance that this emerging exercise model provides. Three groups were evaluated for seven days: the control (no exercise or locomotor limitations), movement-limited flies (MLF) (no exercise, with locomotor limitations), and EXE (with exercise, no locomotor limitations). The EXE flies demonstrated greater endurance-like tolerance in the swimming test, associated with increased citrate synthase activity, lactate dehydrogenase activity and lactate levels, and metabolic markers in exercise. Notably, the EXE protocol regulated the Akt/p38 MAPK/Nrf2 pathway, which was associated with decreased Hsp70 activation, culminating in glutathione turnover regulation. Moreover, reducing the locomotion environment in the MLF group decreased endurance-like tolerance and did not alter citrate synthase activity, lactate dehydrogenase activity, or lactate levels. The MLF treatment promoted a pro-oxidant effect, altering the Akt/p38 MAPK/Nrf2 pathway and increasing Hsp70 levels, leading to a poorly-regulated glutathione system. Lastly, we demonstrated that exercise could modulate major metabolic responses in Drosophila melanogaster aerobic and anaerobic metabolism, associated with apoptosis and cellular redox balance maintenance in an emergent exercise model.